Simulation And Optimization Studies Of Catalyzed Esterification Of Propionic Anhydride With 2-Butanol: Batch Versus Semi Batch Operation. - Rohman, F.S.; Abdul Sata, S.; Aziz, N. (2010)
A model to represent the catalyzed esterification of propionic anhydride with 2-butanol has been developed and simulated.